2017
DOI: 10.1016/j.paid.2017.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Growth mindset of anxiety buffers the link between stressful life events and psychological distress and coping strategies

Abstract: Beliefs about the malleability of global attributes like personality and intelligenceknown as mindsetsare well-established predictors of resilience to challenges in educational contexts. Recent research further suggests that mindsets about anxiety may act in a similar fashion with mental health resilience. In this study we examined whether anxiety mindset would moderate relations between history of stressful life events and psychological distress and coping. Consistent with predictions, relations between numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
88
1
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(108 citation statements)
references
References 22 publications
11
88
1
8
Order By: Relevance
“…The impact of the growth mindset is also significant for personality change and improvement; more specifically, a belief that personality is malleable and can be developed through efforts and education promotes motivation to have better personality [23]. In addition, the significant interaction found in the present study is coherent with previous studies reporting the significant moderating effect of growth mindset on the relationship between stressful life and mental health [37], parenting and subjective well-being [38], and longitudinal change in social anxiety [39]. Thus, it is perhaps the case that having a belief that it is possible to become a morally better person through moral engagement, that is, the moral growth mindset, promotes prosocial engagement significantly.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The impact of the growth mindset is also significant for personality change and improvement; more specifically, a belief that personality is malleable and can be developed through efforts and education promotes motivation to have better personality [23]. In addition, the significant interaction found in the present study is coherent with previous studies reporting the significant moderating effect of growth mindset on the relationship between stressful life and mental health [37], parenting and subjective well-being [38], and longitudinal change in social anxiety [39]. Thus, it is perhaps the case that having a belief that it is possible to become a morally better person through moral engagement, that is, the moral growth mindset, promotes prosocial engagement significantly.…”
Section: Discussionsupporting
confidence: 88%
“…First, given previous studies showing the association between growth mindset and positive motivational outcomes [7,8,24], the main effect of the growth mindset might be significant. Second, as some other studies showed the moderating effect of growth mindset in positive youth development [37][38][39][40], the moral growth mindset might also play a significant role as a moderator. Thus, we were interested in whether the main effect or interaction effect of the moral growth mindset influenced service engagement.…”
Section: The Current Studymentioning
confidence: 86%
“…The goal of our instruction was to develop student writing while also supporting student success. We approached the latter through an emphasis on developing a growth mindset, which views frustration, anxiety, and time challenges not as impediments but as opportunities to develop (Duckworth, 2016;Dweck, 2016;Schroder et al, 2017). This study was implemented in two 12-week third-year undergraduate history courses in one academic year.…”
Section: Methodsmentioning
confidence: 99%
“…To accomplish this, introducing students to the concept of a growth-mindset, or the belief that a person's skills or qualities are not innate but rather develop over time can be an important part of peer review (Dweck, 2016). In the field of positive psychology, a growth mindset has been linked to the development of grit and more comprehensive coping strategies around anxiety and distress (Duckworth, 2016;Schroder et al, 2017).…”
Section: Resiliencementioning
confidence: 99%
“…Praise and encouragement for concrete effort and persistence can help children to learn and adopt effective strategies for learning. A range of studies document that growth mindset makes a positive difference in student and adult achievement, both short-term and long-term (Schroder et al, 2017a(Schroder et al, , 2017bYeager et al, 2016).…”
Section: Stoical Approachesmentioning
confidence: 99%